(untitled) (Journal of the College of Basic Education, 2023)
The current study aimed to know the effect of injecting sustanon, which is one of the compoundsAnabolic steroids as well as sesame oil on some physiological functions in male liverRats, which included measuring the levels of liver enzymes (8, 567, 5607), whileThe histopathological study included histopathological changes caused by sustanonand sesame oil in rat livers. The experimental animals included 25 male rats of the type L-PWhich was divided into five additional groups (5018:0005) equally. groups includednegative control (feed and water); The second group was a positive control (1 ml / kg of weightThe body sesame oil in a low dose (the third group, positive control) 2 ml / kgBody weight: high dose sesame oil (group IV sustanon) 10 mg/kgof body weight (low dose); Fifth group Sustanon (20 mg / kg ofbody weight (high dose). Animal groups were injected weekly for 6 weeks with stanonAnd sesame oil intramuscularly, then killed at the end of the sixth week. The results showed a significant increase(0>0.05) in the levels of liver enzymes [57,8](, 607k) in the groups.injected with Stanon (10 and 20 mg / kg of body weight). While my group showed